Capital Inflow Surges in Emerging Economies: How Worried Should LAC Be? - Andrew Powell; Pilar Tavella (Inter-American Development Bank (IDB), 2012)
This paper analyzes capital inflow surges in emerging economies from 1980 to 2005. Estimated probit models are used, which discriminate well between surges associated with banking crises or recessions, and those surges that end without such events. The results indicate that the composition of inflows and the extent of financial reform are significant determinants of outcomes. Estimated models are applied to the Latin American post-2005 inflow surge and find relatively high estimated probabilities for banking crises and recessions. This suggests that recent inflow surges characterized by high portfolio and banking inflows are a potential cause for concern and that the results constitute a prima facie case for macro prudential interventions.
Keywords: C25; E44; F34; G01; 330